Salamanders on the bench – A biocompatibility study of salamander skin secretions in cell cultures. (1st September 2017) - von Byern, Janek; Mebs, Dietrich; Heiss, Egon; Dicke, Ursula; Wetjen, Oliver; Bakkegard, Kristin; Grunwald, Ingo; Wolbank, Susanne; Mühleder, Severin; Gugerell, Alfred; Fuchs, Heidemarie; Nürnberger, Sylvia
Abstract: Salamanders have evolved a wide variety of antipredator mechanisms and behavior patterns, including toxins and noxious or adhesive skin secretions. The high bonding strength of the natural bioadhesives makes these substances interesting for biomimetic research and applications in industrial and medical sectors. Secretions of toxic species may help to understand the direct effect of harmful substances on the cellular level. In the present study, the biocompatibility of adhesive secretions from four salamander species ( Plethodon shermani, Plethodon glutinosus, Ambystoma maculatum, Ambystoma opacum ) were analyzed using the MTT assay in cell culture and evaluated against toxic secretions of Pleurodeles waltl, Triturus carnifex, Pseudotriton ruber, Tylototriton verrucosus, and Salamandra salamandra . Their effect on cells was tested in direct contact (direct culture) or under the influence of the extract (indirect exposure) in accordance with the protocol of the international standard norm ISO 10993-5. Human dermal fibroblasts (NHDF), umbilical vein endothelial cells (HUVEC), and articular chondrocytes (HAC), as well as the cell lines C2C12 and L929 were used in both culture types. While the adhesive secretions from Plethodon shermani are cytocompatible and those of Ambystoma opacum are even advantageous, those of Plethodon glutinosus and Ambystoma maculatum appear to be cytotoxic to NDHF and HUVEC. Toxic secretions from Salamandra salamandra exhibited harmful effects on all cell types. Pseudotriton ruber and Triturus carnifex secretions affected certain cell types marginally; those from Pleurodeles waltl and Tylototriton verrucosus were generally well tolerated. The study shows for the first time the effect of salamander secretions on the viability of different cell types in culture. Two adhesive secretions appeared to be cell compatible and are therefore promising candidates for future investigations in the field of medical bioadhesives. Among the toxic secretions tested, only two of the five had a harmful effect on cells, indicating different cell toxicity mechanisms. Highlights: The biocompatibility of adhesive salamander secretions was evaluated in comparison to toxic secretions. Some bioadhesives are fully biocompatible in cell cultures and promising candidates as biomaterial. Some other bioadhesives have a cytotoxic effect, contradicting a biocompatibility of bioadhesives per se. The in vitro experiments showed different response of the tested cell types.